Building sites and footing preparation - International Code Council ([Illinois] : International Code Council, 2006)
This video covers basic requirements for building site and footing preparation including basic characteristics of soils, soil investigation reports, location of a building on a lot or building site, footing and foundation requirements, construction for footings and foundations in the IRC and special requirements for concrete footing
Host: Jimm Powell
DVD format
Keywords: Building sites; Buildings -- Specifications; Construction industry